Anthologizing classical Chinese poetry in the twentieth and twenty-first centuries: poetics and ideology - Feng, Wang; Washbourne, Kelly (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
We seek in this study to consider anthologizing as a decision-making activity, marshalling evidence from texts and paratexts reflecting anthologists’ poetic and ideological criteria for selection; to analyze the construction of a national literature accomplished through text selection and omission; and to provide evidence of the systematicity and intertextuality of anthologized texts as interrelated ecologies. We will focus largely on translation history decisions and procedures such as selection and the anthologists’ rationale; presentation format (monolingual, bilingual, the use of Chinese); provenance (direct or indirect translation); and target audience. In exploring criteria for selection, we intend to shed light on the complex problem of representativeness. We posit that anthologizing and its canon-forming and canon-redefining choices appear dialogically, in conversation with various kinds of previous texts, which serve as a kind of “original” to the anthologist’s “translation.” Our corpus includes multi-author anthologies of classic Chinese poetry that were published from the 1890s to the present.